KERJA SAMA ANTARDAERAH PEMERINTAH PROVINSI JAWA BARAT DENGAN PEMERINTAH KOTA DEPOK DALAM PENANGANAN COVID-19 - Galih Adyatma Alaufa; R Slamet Santoso; Retna Hanani (Journal of Public Policy and Management Review, 2022)
Handling COVID-19 is very complex. Therefore, West Java Province and Depok City need to work together to deal with COVID-19 through hierarchical relationships. This study aims to describe the implementation of interregional cooperation and identify the factors that support and hinder the implementation of interregional cooperation. This study uses descriptive qualitative methods, with data collection techniques interview, observation, documentation, and literature study with primary and secondary data sources. The results of this study indicate that the cooperation that has been carried out includes cooperation with third parties, vaccinations, work programs, budgets, legal products, medical equipment, and delegation of human resources. This can be realized through the participation of high stakeholders, the commitment of local leaders, and the absence of local egos. Meanwhile, the obstacles are differences in regulations, lack of discipline, gaps in results (data), and incompetent human resources